Determinants of corporate demand for Islamic insurance in Malaysia - Abdul Hamid, Mohamad; Osman, Jamil; Amin Noordin, Bany Ariffin (Faculty of Economics and Management, Universiti Putra Malaysia, 2009)
This study is the first attempt to empirically investigate the determinants of corporate demand for Islamic insurance (takaful) using data from main board of public listed companies at Bursa Malaysia. Factors like leverage, growth opportunities, expected bankruptcy costs, company size, managerial ownership, tax considerations and regulated effects have been examined in this study. The data covers a five-year period from year 2002 – 2006. The findings show that leverage, expected bankruptcy costs, tax considerations, company size, and managerial ownership play an important role in determining the corporate demand for Islamic insurance in Malaysia. Our conclusions are robust to alternative specifications model of GLS with Fixed Effects that help us to control for unobservable heterogeneity.